(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Poverty is common throughout the state, and a considerable portion of the country populationis eligible for government assistance. Many kids never finish elementary education, and particulargroups have poor enrollment rates in high schools. This is notably true for females, who are more likelyto drop out of upper elementary school, as well as girls and boys from SC and ST. Social isolation,poverty, and child marriage are just a few of the important challenges that prevent female students fromenrolling in and studying in school. The study’s suggestions will help the Madhya Pradesh governmentbuild on the gains it has already made in increasing elementary and secondary school enrollment andretention rates.